The effects of continuous support program during labor by nurses on pain levels and pain coping behaviors in primiparous women who received misoprostal in Fang Hospital, Chiang Mai province - Tongdang, Piyanan (Journal of Nakornping Hospital, 2021)
This quasi-experimental research aims to examine the continuous labor support program during labor by nurses on pain levels and pain coping behaviors in primiparous women who received misoprostal. Sample were 70 primiparous women who received misoprostal and attended at delivery room, Fang Hospital. Purposive sampling was used to recruit sample. They were divided into an experimental group (n=35) and control group (n=35). The experimental group received continuous labor support program and routine nursing care. The control group received routine nursing care. Research instruments consisted of the continuous labor support program, primirarous manual, personal profile recording form, a numeral rating scale for pain levels and pain coping behavior observation form. The data were analyzed by using descriptive statistics and The Mann-Whitney U test. The findings revealed that the experimental group had the level score of pain during cervical dilatation less than 4 centimeter, 4-7 centimeter and 8-10 centimeter statistically significantly less than the control group (Z = -3.77, p < .001, Z = -3.05, p < .001, Z = -4.63, p < .001, respectively) and had pain coping behavior score during cervical dilatation less than 4 centimeter, 4-7 centimeter and 8-10 centimeter statistically significantly more appropriate than the control group (Z = -2.70, p = .004, Z = -3.95, p < .001, Z= -4.76, p < .001, respectively ). This study confirmed the effective of the continuous labor support program could reduce labor pain and increase pain coping behavior. Therefore, hospitals should be used this program to care laboring women who received misoprostal.